2021
DOI: 10.3390/nu13072448
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Anti-inflammatory Effects of Asiatic Acid in a DNCB-Induced Atopic Dermatitis Animal Model

Abstract: We examined the immunomodulatory and anti-inflammatory effects of asiatic acid (AA) in atopic dermatitis (AD). AA treatment (5–20 µg/mL) dose-dependently suppressed the tumor necrosis factor (TNF)-α level and interleukin (IL)-6 protein expression in interferon (IFN)-γ + TNF-α-treated HaCaT cells. The 2,4-dinitrocholrlbenzene (DNCB)-induced AD animal model was developed by administering two AA concentrations (30 and 75 mg/kg/d: AD + AA-L and AD + AA-H groups, respectively) for 18 days. Interestingly, AA treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
(62 reference statements)
0
8
0
1
Order By: Relevance
“…Asiatic acid levels amongst CPE were 15-fold greater than that of NECP. Asiatic acid has also been reported to have immunomodulatory effects (47).…”
Section: Complex Interplay With Neuroendocrinological Neuroimmune Fac...mentioning
confidence: 99%
“…Asiatic acid levels amongst CPE were 15-fold greater than that of NECP. Asiatic acid has also been reported to have immunomodulatory effects (47).…”
Section: Complex Interplay With Neuroendocrinological Neuroimmune Fac...mentioning
confidence: 99%
“…Mast cells contribute to allergic reactions through the production and secretion of proinflammatory mediators such as histamine, chemokines, cytokines, and growth factors. Moreover, mast cells actively contribute to modulating the function of naive T cells, thereby increasing T-cell activation [ 2 ]. The current study revealed that TMTH administration significantly decreased mast cell infiltration in DNCB-treated mice ( Figure 5 E).…”
Section: Discussionmentioning
confidence: 99%
“…Eczema, widely known as atopic dermatitis (AD), is a chronic inflammatory skin disease associated with several symptoms, including swelling, cracked skin, erythema, and pruritus [ 1 , 2 ]. This chronic, recurrent, and hereditary allergic skin condition has become a major global health concern owing to its increasing prevalence worldwide [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many literature reports on its antiinflammatory, antitumor, and antidiabetic properties [8][9][10][11]. Specifically, its anti-inflammatory properties are very promising [12,13]. Studies have found that AA can limit liver fibrosis in rats, but there are few reports on the effect of AA in alcoholic hepatitis.…”
Section: Introductionmentioning
confidence: 99%